2022
DOI: 10.1002/for.2860
|View full text |Cite
|
Sign up to set email alerts
|

Modeling credit risk with a multi‐stage hybrid model: An alternative statistical approach

Abstract: This paper examines the impact of hybridizations on the classification performances of sophisticated machine learning classifiers such as gradient boosting (GB, TreeNet ® ) and random forest (RF) using multi-stage hybrid models. The empirical findings confirm that, overall, hybrid model GB (X* Di ; Ŷ Di, LR ), which consists of TreeNet ® combined with logistic regression along with a new dependent variable, offers significantly superior accuracy compared to the baselines and other hybrid classifiers. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Jones et al (2015) found that generalized boosting, AdaBoost, and random forest methods are superior to other leading popular credit prediction methods, such as neural networks and SVMs. Jones (2017), Uddin et al (2022), Jiang and Jones (2018), Cheng et al (2018), andJones andWang (2019) apply the advanced version of gradient boosting model, TreeNet ® , to the field of credit risk research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jones et al (2015) found that generalized boosting, AdaBoost, and random forest methods are superior to other leading popular credit prediction methods, such as neural networks and SVMs. Jones (2017), Uddin et al (2022), Jiang and Jones (2018), Cheng et al (2018), andJones andWang (2019) apply the advanced version of gradient boosting model, TreeNet ® , to the field of credit risk research.…”
Section: Literature Reviewmentioning
confidence: 99%